Pengaruh Kemudahan Penggunaan, Kegunaan, Persepsi Risiko, Dan Kenyamanan Terhadap Sikap Konsumen Dalam Belanja Online - Hakam Ali Niazi; Retno Fuji Oktaviani (Jurnal Bintang Manajemen, 2023)
This study aims to determine: (1) the effect of ease of use on consumer attitudes in online shopping at online Lazada.com stores, (2) the effect of usability on consumer attitudes in online shopping at Lazada.com online stores, (3) the effect of risk perception on consumer attitudes in online shopping at online stores at Lazada.com, (4) the influence of convenience on consumer attitudes in online shopping at online Lazada.com stores, and (5) the influence of ease of use, usability, risk perception and convenience on consumer attitudes in online shopping at Lazada.com online store. The population in this study are internet users in Tangerang. The sampling technique used in this study was purposive sampling with a sample size of 200 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The analysis technique used is multiple regression. The results show that: (1) there is a positive effect of ease of use on consumer attitudes in online shopping, (2) there is a positive effect of usefulness on consumer attitudes in online shopping (3) there is a positive effect of risk perception on consumer attitudes in online shopping (4) there is a positive influence of convenience on consumer attitudes in online shopping.